The Significance of North Norway to NATO Military Strategy. - Scheider, Max B. (1973)
The purpose of the report was to develop an appraisal of North Norway in order to determine the order of significance which should be attached to it in developing NATO strategy. Information was gathered from a literature search and from visits to the area while the author was assigned to the staff of Allied Command Northern Europe. While lacking vital intrinsic value, North Norway provides NATO with a base for forward surveillance and operations. It would be especially valuable for operations to block the sea routes between the Atlantic and the Soviet naval base complex in the Murmansk area. In addition, the credibility of NATO's collective security assurances would be seriously damaged if any NATO territory were occupied. (Modified author abstract)